Evaluation of the effect of a nurse-led vestibular rehabilitation program enriched with yoga on knowledge levels and vertigo symptoms in patients with vertigo - Gayathri Selvaraj; Santhanasamy Punitha; Ganesan Dayanidy; Ananda Balayogi Bhavanani (MGM Journal of Medical Sciences, 2024)
Background: Around 9.9 million people in India experience vertigo or dizziness, making it difficult to perform daily activities. The aim of this study was to evaluate the effectiveness of nurse-led vestibular rehabilitation programs enriched with yoga on the level of knowledge and vertigo symptoms among patients with vertigo. Materials and Methods: Eighty patients were selected through purposive sampling, and 40 each were randomly assigned to the experimental and control groups. The experimental group received a nurse-led vestibular rehabilitation program comprising vestibular exercises and designated yoga routines. By contrast, the control group received standard care, including prescription of drugs by the physician and follow-up. Data collection involved structured instruments, including sociodemographic and clinical variables, a multiple-choice questionnaire to gauge knowledge levels, and a 5-point Likert scale to measure the intensity of vertigo symptoms. Statistical analysis was conducted using descriptive and inferential methods with IBM Statistical Package for the Social Sciences (SPSS), version 21 (Chicago, Illinois, USA). Results: The independent t value for comparing post-test knowledge (t = 16.87, P = 0.00) and vertigo symptoms (t = 9.25, P = 0.00) between the experimental and control groups indicated significant differences at a significance level of P < 0.001. Conclusion: Incorporating yoga into a nurse-led vestibular rehabilitation program effectively improved the knowledge level and reduced vertigo symptoms among patients experiencing vertigo.